Pengaruh Metode Latihan Melalui Pendekatan Holistik Terhadap Peningkatan Kemampuan Aerobik Pemaib Sepakbola FIK UNM. - Juhanis Juhanis; Sudirman Sudirman; Hasmiyati Hasmiyati (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
Aerobic Ability FIK UNM football players are still not maximal. This study aims to determine the effect of training methods through a holistic approach to increasing the aerobic ability of FIK UNM football players. This research is an experimental research, the research design used is “One Group Pretest-Posttest”. The population of this study were all football players at FIK UNM and the sampling technique used purposive sampling, with a total sample of 20 football players at FIK UNM. The instrument used for data collection on aerobic ability in this study was the multistage test. The data analysis technique used the t test with a significant level of 5%. Based on the results of the research and discussion, the results of the analysis of the t test for the effect of the training method through a holistic approach to increasing the aerobic ability of FIK UNM football players obtained tcount (17.688)> ttable (1.83). Thus it can be concluded that there is an effect of training methods through a holistic approach that is positive and significant on the aerobic ability of FIK UNM football players. Based on the difference in the average results (mean difference) from the pretest and posttest, it can be seen that the percentage increase in the aerobic ability of FIK UNM football players is 15.66%.